2013
DOI: 10.1097/pas.0b013e318272ff4d
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of HER-2 Positivity in Rectal Cancer and Prognosis

Abstract: In patients with advanced rectal cancer (cUICC II and III) multimodality therapy resulted in better long-term local tumor control. Ongoing clinical trials are focusing on therapy intensification to improve disease-free (DFS) and cancer-specific survival (CSS), the integration of biomarkers for prediction of individual recurrence risk, and the identification of new targets. In this context, we investigated HER-2, a member of the epidermal growth factor receptor family, whose expression pattern and role was uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 40 publications
7
57
0
2
Order By: Relevance
“…Out of these excluded studies, one shared the same population with another study , two analyzed HER-2/neu expression in serum (Tsigris et al, 2002;Kovacevic et al, 2007), and patients number of HER-2/neu overexpression of one was less than three (Pappas et al, 2013). Finally, 17 eligible studies were included into this meta-analysis (Kay et al, 1994;Kapitanovic et al, 1997;Osako et al, 1998;Knosel et al, 2002;McKay et al, 2002;Rossi et al, 2002;Sanz-Casla et al, 2004;Essapen et al, 2004;Jesus et al, 2005;Uner et al, 2005;Schuell et al, 2006;Park et al, 2007;Kavanagh et al, 2009;Li et al, 2011;Conradi et al, 2013;Lim et al, 2013). Figure 1 shows a flowchart of the literature selection process.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Out of these excluded studies, one shared the same population with another study , two analyzed HER-2/neu expression in serum (Tsigris et al, 2002;Kovacevic et al, 2007), and patients number of HER-2/neu overexpression of one was less than three (Pappas et al, 2013). Finally, 17 eligible studies were included into this meta-analysis (Kay et al, 1994;Kapitanovic et al, 1997;Osako et al, 1998;Knosel et al, 2002;McKay et al, 2002;Rossi et al, 2002;Sanz-Casla et al, 2004;Essapen et al, 2004;Jesus et al, 2005;Uner et al, 2005;Schuell et al, 2006;Park et al, 2007;Kavanagh et al, 2009;Li et al, 2011;Conradi et al, 2013;Lim et al, 2013). Figure 1 shows a flowchart of the literature selection process.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…However, the more likely reason may be the various scoring systems used, considering that four different criteria were reported in the five studies of the Asian subgroup. In addition, it is worth noting that Conradi et al (2013) showed that HER-2 overexpression was a good predictive factor. They reported that patients with HER-2 positivity showed a trend towards a better disease-free survival and a benefit in cancer-specific survival, and the 5-year survival rate was 96.0% (HER-2 positive) versus 80.0% (HER-2 negative).…”
Section: Discussionmentioning
confidence: 99%
“…Five different cut-off values were used to determine HER-2 status, of which the HercepTest scoring system was the most frequently adopted (n=5). As for prognostic value, five studies identified HER-2 overexpression as an indicator of poor prognosis (Osako et al, 1998;Park et al, 2007;Baiocchi et al, 2009;Chen et al, 2010;Lu et al, 2012), five studies revealed that HER-2 overexpression had no influence on CRC survival (McKay et al, 2002;Rossi et al, 2002;Jesus et al, 2005;Kavanagh et al, 2009;Li et al, 2011), and one study reported HER-2 overexpression to be a good predictor (Conradi et al, 2013) (Table 2).…”
Section: Literature Search and Characteristics Of The Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Einige seltene histologische Subtypen wie das muzinöse Adenokarzinom und das rhabdoide Karzinom haben eine ungünstigere Prognose und sprechen schlecht auf eine präoperative Radiochemotherapie an. Zu den näher untersuchten und immunhistochemisch im Gewebe bestimmbaren Parametern mit potenzieller Relevanz zählen HER-2 [4], Thymidilatsynthase [29], Survivin [27], Topoisomerase I [13], Amphiregulin (AREG) und ERCC1 [25]. Für einige dieser Marker wurde eine Korrelation mit dem Ansprechen auf bestimmte Pharmaka beschrieben.…”
Section: Prädiktion Des Ansprechens Auf Neoadjuvante Therapieunclassified